2015
DOI: 10.1097/mpg.0000000000000668
|View full text |Cite
|
Sign up to set email alerts
|

MMPs‐2 and ‐14 Are Elevated in Eosinophilic Esophagitis and Reduced Following Topical Corticosteroid Therapy

Abstract: Background Eosinophilic esophagitis (EoE) is a chronic antigen mediated disease in children and adults associated with substantial esophageal remodeling and fibrosis. The expression of the remodeling-associated matrix metalloproteinases (MMPs) has not been previously detailed in EoE. Methods MMP-2 and -14 expression and cellular localization was assessed using qPCR and immunohistochemistry/immunofluorescence in EoE fibroblasts, active and inactive pediatric EoE biopsies, and non-diseased control biopsies. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…We have previously reported that MMP-14 is also increased in the epithelium of pediatric EoE subjects (16). Like PAI-1, MMP-14 expression and release is increased in epithelial cells by TGFβ1 (16).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…We have previously reported that MMP-14 is also increased in the epithelium of pediatric EoE subjects (16). Like PAI-1, MMP-14 expression and release is increased in epithelial cells by TGFβ1 (16).…”
Section: Discussionmentioning
confidence: 89%
“…Like PAI-1, MMP-14 expression and release is increased in epithelial cells by TGFβ1 (16). Indeed, PAI-1 gene expression correlates positively with MMP-14 gene expression as well as with the expression of a number of other remodeling genes including collagen I, MMP-2, Ki67, vimentin, and TGFβ1.…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells are produce of TGFβ1 in EoE. TGFβ1 increases pro-fibrotic gene expression and induces esophageal smooth muscle cell contraction [ 31 , 32 ]. We found that there was a step-wise gradient of mast cell numbers by genotype with TT genotype being the highest in the context of SPT positivity to foods.…”
Section: Discussionmentioning
confidence: 99%
“…TGFβ also induces a number of other profibrotic tissue remodeling factors including MMPs, plasminogen activator inhibitor 1 (PAI-1) and Periostin. MMP2 and MMP14 are upregulated in EoE and in patients responding to corticosteroid therapy [39]. PAI-1 has also been found to be upregulated in active EoE patient biopsies and its expression correlates with lamina propria fibrosis.…”
Section: Mechanisms Of Fibrosis In Eoementioning
confidence: 99%